(untitled) (UNED Research Journal, 2020)
Introduction: El Salvador is one of the most densely populated and most deforested countries of the American continent, where social insecurity make field research difficult. Here we present an experience in which rural and indigenous communities were part of a mammal survey. Objectives: To identify the mammals of Río Sapo basin, and establish the potential of local communities in scientific studies of mammals in El Salvador. Methods: We studied 17 sites in Joateca and Arambala, Río Sapo basin; 14 volunteers were organized, including local former hunters, forest owners, indigenous communities, and researchers. Fieldwork was done from August 2018 to December 2019. Mammals were identified during field visits and with camera traps. We also included the socio-cultural importance of wildlife within the Kakawira-Lenca indigenous worldview. Results: Twenty-two species were identified, including six that are threatened or endangered. We expanded the local range of Tamandua mexicana and Pecari tajacu for the department of Morazán, also, we added Glaucomys volans to the country’s species list. We list traditional uses of mammals of the Kakawira-Lenca culture and report the indigenous names of 15 species. Conclusion: The participation of local communities is a valid option for field work in El Salvador, and probably in other areas where social insecurity makes field research dangerous.